Urgensi Pemberian Tambahan Penghasilan terhadap Kepuasan dan Kinerja - Maman Sulaeman; Erna Rusmiwati; Endang Syarif; Yayan Rudianto; Wahdan Budi Setiawan (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
Employee performance is always a problem for every organization. Private and government organizations are trying to improve the performance of their human resources. This study aims to analyze the urgency of providing additional income to satisfaction and performance. The research method is used quantitatively by collecting data through a questionnaire distributed to 354 ASNs in the Banjar city government. It was further analyzed using SEM PLS. The results of the study found that providing additional income for ASNs can improve satisfaction and performance. ASN becomes satisfied with the receipt of additional income so that it can improve its performance.